The Role Of Games In Supporting Child Growth And Development Holistically - Anisa Nopriyani; Ali Akbarjono; Budrianto (Yayasan Azhar Amanaa Yogyakarta, 2025)
Play is an essential component of early childhood life, functioning both as a learning medium and as a strategy to stimulate children’s holistic development. This study aims to examine the role of play in supporting the comprehensive growth and development of children in Islamic Early Childhood Education (PIAUD). The research employed a library research method with a descriptive qualitative approach. Data were collected from various sources, including books, scientific journals, research articles, and other relevant academic documents related to play and early childhood development. Data analysis was conducted using content analysis techniques, which involved collecting, reviewing, and interpreting literature related to play and child development in early childhood education. The findings of the study indicate that play has a significant and multidimensional role in supporting children’s physical, motor, cognitive, language, social-emotional, creative, as well as moral and spiritual development. In the context of Islamic Early Childhood Education (PIAUD), play also serves as an effective medium for instilling Islamic values. Various educational play activities, such as learning Hijaiyah letters, practicing daily prayers, exploring stories of the Prophets, and engaging in games that promote Islamic character building, contribute to the development of children’s moral and spiritual foundations. Therefore, play can be considered an effective and essential learning strategy to support optimal, balanced, and holistic child development in accordance with the objectives of Islamic Early Childhood Education (PIAUD).